Psoriasis- its Presentation and Modalities of Management - Hossain, MM; Mahmood, I; Newaz, MS (TAJ: Journal of Teachers Association, 2009)
Psoriasis is common (with 2% prevalence) chronic inflammatory papulosquamous disorder of the skin and nails with or- without the joint involvement .The exact cause is still illusive but the disorder has distinct genetic predisposition with some environmental factors triggering the clinical expression and the immunological aberration playing a pathogenic role. Psoriasis is not contagious but can be inherited. Psoriasis needs long-term treatment. The different modalities of management are self-care at home, medical treatment, phototherapy using UV-8 in the Goeckermanregimen and Ingram method and PUV-A therapy may be given according to the types of psoriasis and facilities available. TAJ 2009; 22(1): 298-301